Diseño e implementación de un sistema de comercio electrónico para las PIMES. - Aguirre Maza, Jefferson Alexander (2021)
The creation and maintenance of websites made through the use of traditional programming languages require the investment of economic resources related to trained technical personnel. The SGC constitute an alternative that simplifies this work by offering tools that focus the effort of the people in charge, on the content of the sites rather than on their technical aspect. Being the Content Management Systems, a type of collaborative development tools also offer the advantage of allowing the updating of the sites by more than one person, as well as the application of design standards, just as their consistency, are guaranteed since that with a SGC the style or interface of the website is not structurally manipulated, only its information. The use of open source management systems, in addition to the advantages described, offer the possibility of developing new functions in the QMS that are useful for each organization. 5 Without a doubt, the cost reduction that these systems offer is fundamental, as well as the support that the multiple user communities provide by sharing information and solving the most frequent problems.